Russian Federation : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The Selected Issues paper on the Russian Federation discusses the economic growth and future growth potential of the country. After almost a decade of impressive growth performance, Russia suffered a sharp contraction in 2009 with GDP falling by 8 percent. This paper gives an overview of the conceptual issues regarding potential growth and the analytical framework based on an exogenous growth model; growth accounting results for Russia in the past decade; and importance of structural reforms to achieve sustained high growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet